Representation Of The "Self" And "Other" Of Arab Spring Reporting In CNN And AJE'S Online News Articles - Al Radhi, Hanan Hasan Abdul-Razzaq (2017)
This study aimed to explore the situation often referred to as the 'Arab spring' that prevailed in the Arab world after 2010-2011 by analyzing CNN and AJE's online news articles released in their websites 2013. The main concern of the study is to unveil the two well-known agencies' ideologies in relation to the Arab spring upheaval and to discover how their media discourse has been manipulated to control people's minds with respect to countries involved in the Arab spring, namely, Tunisia, Egypt, Libya and Syria.